The development Of Islamic engineering Sciences: a prelude - Shuriye, Abdi Omar (Institute of Islamic Understanding Malaysia, 2004)
During the Prophetic epoch and that of the rightly guided Caliphs along with the Umayyad period, Muslims were more concerned with safeguarding lands, setting up administrative, fiscal and legal systems. As a result the scientific legacy of engineering sciences had remarkably advanced only in later period, the Abbasid period. The Umayyad dynasty however, upon assuming rulership they engaged themselves with some civil engineering activities by building Damascus, their main administrative capital. The Abbasid Caliphate took over from the Umayyad and moved their administrative activity to Baghdad. Al-Mansur ("154-75), the second Abbasid caliph, built the fabulous new city of Baghdad, the engineering of Baghdad was the first astronomical test the Abbasid Caliph has to perform. Nawbakht and Masha'allah, the two famous astronomers assisted al-Mansur in supervising the fundamental settings of Baghdad. Al-Mansur entrusted both of the aforementioned astronomers in planning for the city but maintained a close supervision over the construction of the city. It was civil engineering sciences that were prominent during this period. This observation aims at highlighting the facets and elemental developments of early Islamic engineering sciences and relates those developments to the current contentions of formative Islamic engineering practices and perspective orientations.